Cases on critical practices for modern and future human resources management - Akella, Devi, 1974-; Eid, Niveen, 1983-; Sabella, Anton, 1975- (Advances in human resources management and organizational development (AHRMOD) book series., 2021)
"This edited volume, a collection of corporate case studies from across the world, critically reviews different aspects of human resources management, its origin, role and responsibilities, functions and the future of human resources management in the context of changing patterns of work, society and the world"--